Technology, Design and the Arts - Opportunities and Challenges - Earnshaw, Rae; Liggett, Susan; Excell, Peter; Thalmann, Daniel (Springer Series on Cultural Computing, 2020)
This open access book details the relationship between the artist and their created works, using tools such as information technology, computer environments, and interactive devices, for a range of information sources and application domains. This has produced new kinds of created works which can be viewed, explored, and interacted with, either as an installation or via a virtual environment such as the Internet. These processes generate new dimensions of understanding and experience for both the artist and the public's relationships with the works that are produced. This has raised a variety of interdisciplinary opportunities and issues, and these are examined. The symbiotic relationship between artistic works and the cultural context in which they are produced is reviewed. Technology can provide continuity by making traditional methods and techniques more efficient and effective. It can also provide discontinuity by opening up new perspectives and paradigms. This can generate new ideas, and produce a greater understanding of artistic processes and how they are implemented in practice. Tools have been used from the earliest times to create and modify artistic works. For example, naturally occurring pigments have been used for cave paintings. What has been created provides insight into the cultural context and social environment at the time of creation. There is an interplay between the goal of the creator, the selection and use of appropriate tools, and the materials and representations chosen. Technology, Design and the Arts - Opportunities and Challenges is relevant for artists and technologists and those engaged in interdisciplinary research and development at the boundaries between these disciplines.